Antimicrobial activity and phytochemical studies on Turkish samples of Papaver macrostomum - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2007)
Three alkaloids, cheilantifoline, mecambrine, and laudanosine, and two flavonoids, luteoline and tricine, have been isolated from two samples of Papaver macrostomum Boiss. & Huet ex Boiss. (Papaveraceae) of Turkish origin. Antimicrobial tests have been performed on the extracts obtained from these species. It has been found that diethyl ether and acetone extracts of two samples obtained from the aerial parts of the plant have antimicrobial activity against almost all bacteria tested. The existence of flavonoids and the antimicrobial activity of this species are reported for the first time.
Keywords: alkaloids; antimicrobial activity; cheilantifoline; flavonoids; laudanosine; luteoline; mecambrine; Papaver macrostomum; tricine